(untitled) (Third Sector Social Economic Review, 2013)
In historic due course, while the functions of a state grow, its sources do not increase in a commensurate way, which has made it imperative to search for effectiveness in public expenditures and such quests constituted the main focus of continuous reform initiatives in many countries. In the specter of incrementally expanding economic and financial depressions and the lessons drawn out of economic crises inflicting the world, effectiveness has become a significant building-block in auditing as much as it has been in governance and performance auditing has rapidly developed. As a corollary, crucial functions such as performance auditing which develops in an on-going manner, efficiency and effectiveness in use of public funds, transparency in governance and reinforcement of accountability, enhancement of community welfare and strengthening of citizens act as sine qua non instruments in sustaining viable and democratic governance.